RISK LEVEL ANALYSIS OF GREEN BEAN FARMING PRODUCTION IN THE TRANSMIGRATION AREA OF WEOE VILLAGE, WEWIKU SUBDISTRICT, MALAKA REGENCY - Hakko, Herson M.; Nurwiana, Ida; Un, Paulus (Buletin Ilmiah Impas, 2025)
Mung bean farmers in the transmigration area of ​​Weoe Village, Wewiku District, Malaka District are often faced with various obstacles that result in low production produced by farmers. Therefore, improvement efforts are needed at the farm level to encourage farmers to be more optimal in managing their farms. This research aims to: 1) identify the obstacles faced by green bean farming, 2) determine the income of green bean farmers, and 3) determine the level/magnitude of production risk and efforts to manage production risks of green bean farming in the Transmigration Area of ​​Weoe Village, Wewiku Subdistrict, Malaka District. The survey method was used in this study, the data used were primary data and secondary data. The location of the study was in the Transmigration Area of ​​Weoe Village, Wewiku Subdistrict, Malaka District which was determined purposively, based on the potential for developing production and the area of ​​mung bean land. Samples were taken by simple random sampling of 60 respondents. The analysis method used variance analysis, standard defiation, and coefficient variation. The research results show that (1) The constraints faced by mung bean farmers in the Transmigration Area of Weoe Village include a lack of knowledge about proper mung bean cultivation, inadequate understanding of pest and disease control, weed management, and improper post-harvest handling, which results in low-quality seeds; (2) The farm income from mung bean cultivation amounts to IDR. 124.194.693 with an average income of IDR. 2.069.912 per farmer or IDR. 5.222.653 per hectare; (3) The level of production risk, seed risk, and labor risk in mung bean farming is high, while the risk of land area and pesticide is low. The risks associated with production, land area, seeds, pesticides, and labor in mung bean farming are relatively high. Efforts to mitigate production risks include maintaining soil conditions by clearing land and removing diseased plants, selecting high-quality or disease-resistant seeds, ensuring proper seedling management, taking good care of crops, and developing strong mental resilience to handle unexpected challenges, such as potential financial losses from farming activities.